Microcontroller-based track axle counter system design - Chang, Shuwen; Yan, Shubin; Chen, Zhanbo; Ren, Yifeng (Journal of physics. Conference series, 2024)
Axle counting technology is an extremely important part of many aspects in ensuring the safety of railroad operation. Axle counting equipment is set up on the railroad tracks, and through the operation of sensors, it detects the trains that drive into the train operating area where the axle counting equipment is arranged. A common axle counting system uses a detection device that utilizes a wheel sensor that senses the movement of the wheel cutting through magnetic lines of inductance causing a change in the magnetic field within the zone. This paper introduces a track axle counter system, the system will be a microcontroller as the core, the use of ultrasonic detection in the train interval of the train wheel distance changes, instead of the existing axle counting system using wheel sensors to sense the electromagnetic signals generated by the wheels, to achieve the axle counting and counting function, so as to determine the track occupancy.